Psikologi Keberagamaan: Memahami Dimensi Psikologis dalam Penghayatan Agama - Susilo Wibisono (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
This article aimed to develop an idea on psychology of religiosity as a psychological paradigm on various religious phenomenon.One of important point emphasized in this article is the experience of psychologists in viewing religion as psychological phenomenon. The three important issues on religiosity context in Indonesia are the fundamentalism issue, the relation of religion and mental health and also the discrimination among minority in the name of religion. Keywords : Psychology of religiosity, discrimination, mental health, fundamentalism.